Knowledge, attitude and practice towards dengue prevention among residential students at Tan Sri Mustaffa Babjee college, Universiti Putra Malaysia - Hasrin, Khairun Nadia; Ali, Nina Fatma (Universiti Putra Malaysia Press, 2023)
The aim of this study was to assess the level of knowledge, attitude, and practice towards dengue prevention among students at Tan Sri Mustaffa Babjee College, Universiti Putra Malaysia. Method: An analytical cross-sectional survey was performed with 214 respondents from Tan Sri Mustaffa Babjee College residents using a simple random sampling method. A self-administered validated questionnaire was distributed to respondents through student email and Whatsapp phone application. The acquired data was then analyzed using Statistical Package for Social Sciences Software (SPSS) Version 27. Results: The majority of the students had moderate knowledge (17.14 ± 2.510), attitude (30.69 ± 4.065) and practice (7.97 ± 2.224) towards dengue prevention. The year of study was the only sociodemographic characteristic that had a significant association with knowledge (χ2 = 18.288, P = 0.013), attitude (χ2 = 18.526, P = 0.010) and practice (χ2 = 19.194, P = 0.014) of dengue prevention, while the factor of the study programme (χ2 = 31.599, P = 0.002) were found to have significantly associated with the level of knowledge. Conclusion: There was a significant association between dengue prevention knowledge and practice (χ2 = 11.838, P = 0.019), but no significant association between knowledge and attitude, as well as practice and attitude. College management should organize and regularly implement the dengue control activities that focus on both preventive action and expanding awareness of dengue prevention to ensure lifetime action and effective methods in controlling dengue.